Hinduism before reform - Hatcher, Brian A. (Brian Allison) (Harvard University Press, 2020)
"By the early eighteenth century, the Mughal Empire was in decline and the East India Company was making in-roads into the subcontinent with an eye on spices, indigo, and opium. A century later, Christian missionaries, Hindu "reformers," Muslim saints, and Sikh rebels formed the colorful religious fabric of colonial India. Through a focus on two distinct nineteenth-century Hindu religious communities and their charismatic leaders-the "cosmopolitan" Rammohun Roy and the "parochial" Swami Narayan, whose influences continue to be felt in contemporary Indian religious life-Hatcher tells us the story of how urban and rural people thought about faith, ritual, and gods. Along the way, he sketches a radical new way of thinking about the origins of modern Hinduism. Written as a challenge to the rigid structure of revelation-schism-reform-sect prevalent in much of religious studies, Hinduism Before Reform invites us to reconsider the very idea of religious reform. The category of reform has played an important role in how we think about two of the most influential Hindu movements of the modern era, the Swaminarayan Sampraday of Gujarat and the Brahmo Samaj of Bengal. The lens of reform characterizes the Swaminarayan Sampraday as backward looking in contrast to the progressive modernity of the Brahmo Samaj. From such a comparison flow a host of conclusions about religious modernity and the Indian nation. Hindusim Before Reform asks how things would look if one eschewed the vocabulary of reform entirely. Is there another way to conceptualize the origins and significance of these two Hindu movements, one that does not trap them within the teleology of a predetermined modernity?"--